Shear punch strength evaluation of nanocomposite and compomer, post-conditioning in dietary solvents – An in-vitro study - Harsimran Kaur; Harpreet Singh; K.S. Vinod; Baldeep Singh; Rachita Arora; Sayan Chatopaddhya (Journal of Oral Biology and Craniofacial Research)
Background: Perpetual research in esthetic dentistry has stupendously contributed in improving the mechanical and esthetic properties of restorative materials. Recently introduced nanocomposite claim to possess higher optimized esthetic and mechanical properties superior to other esthetic restorative materials in clinical use. It has been highlighted in many studies that intraoral degradation of composites is a consequence of both mechanical factors and chemical degradation. Thus, this in-vitro study was conducted to determine the strength of commonly used esthetic restorative materials after conditioning them in dietary solvents, thereby, simulating the intraoral environment. Aim: Evaluation of shear punch strength of nanocomposite and compomer, post-conditioning in dietary solvents. Materials and methods: Two test groups mentioned above, each containing sixty preconditioned samples, divided into four subgroups of fifteen samples each and conditioned in different dietary solvents, were subjected to shear punch test in custom designed shear punch apparatus in Universal Testing Machine. Results: Among the dietary solvents, citric acid caused maximum decrease in the strength while conditioning in heptane showed increase in strength of the test restorative materials. Conclusion: Nanocomposite revealed to have higher strength, thereby indicating its better application universally.